2020
DOI: 10.1186/s13048-020-00650-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glutamine on Dehydroepiandrosterone-induced polycystic ovary syndrome rats

Abstract: Background Previous studies have shown that chronic inflammation and oxidative stress may play an important role in the pathophysiology of polycystic ovary syndrome (PCOS), and glutamine (Gln) have showed the anti-inflammatory and antioxidant properties. So the aim of this study is to investigate the effect of glutamine supplementation on PCOS rats. Methods Female Sprague–Dawley rats were randomly assigned into four groups (n = 10 /group), control group, PCOS group, PCOS+ 0.5 g/kg Gln group and PCOS+ 1.0 g/kg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
5
11
0
Order By: Relevance
“…DHEAS level tended to be higher in PCOS women. Also, there was a correlation between age, BMI, IL-6 level, and DHEAS level as recent studies (25). As a result, our results suggest that endocrine hormone concentrations were significantly higher in PCOS.…”
Section: Discussionsupporting
confidence: 88%
“…DHEAS level tended to be higher in PCOS women. Also, there was a correlation between age, BMI, IL-6 level, and DHEAS level as recent studies (25). As a result, our results suggest that endocrine hormone concentrations were significantly higher in PCOS.…”
Section: Discussionsupporting
confidence: 88%
“…A study reported that human ovarian tissue was cryopreserved using freezing medium supplemented with cryoprotectants and antioxidants (L-glutamine and taurine) and exhibited good preservation of ovarian vascular integrity and functionality of granulosa cells post thawing [41]. Furthermore, the glutamine supplementation could effectively alleviate in ammatory reaction and oxidative stress in PCOS rats [40] and protect Chinese hamsters from radiation damage [42]. Thus, the relationships among the levels of Gln in follicular uid, cumulus GC function, and oocyte development are worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…A research found that Gln was used as an additive substance to enhance antioxidant capacity in the breast muscle of heat-stressed broilers [38]. Moreover, Gln improves the body's resistance to stress [39] and restores the ovarian function of PCOS rats [40]. In addition, Gln, as the main energy supply substance for mitochondria to form ATP, is an important source of energy for oocyte maturation and the development of embryo [34].…”
Section: Discussionmentioning
confidence: 99%
“…A research found that Gln was used as an additive substance to enhance antioxidant capacity in the breast muscle of heat-stressed broilers [42]. Moreover, Gln improves the body's resistance to stress [43] and restores the ovarian function of PCOS rats [44]. In addition, Gln, as the main energy supply substance for mitochondria to form ATP, is an important source of energy for oocyte maturation and the development of embryo [38].…”
Section: Discussionmentioning
confidence: 99%
“…and exhibited good preservation of ovarian vascular integrity and functionality of granulosa cells post thawing [45]. Furthermore, the glutamine supplementation could effectively alleviate in ammatory reaction and oxidative stress in PCOS rats [44] and protect Chinese hamsters from radiation damage [46]. Thus, the relationships among the levels of Gln in follicular uid, cumulus GC function, and oocyte development are worthy of further study.…”
Section: Discussionmentioning
confidence: 99%